"Investigation into the use of freon 12 as a working medium in a high-speed wind-tunnel" - Pozniak, O. M. (College of Aeronautics, 1957)
The Freon 12 tunnel project at the College of Aeronautics was started to pin experience in the design of such tunnels and subsequently to investigate their use for aerodynamic measurements and the correlation of these with similar measurements in air. Reports dealing with the use of heavy gases are listed and the factors affecting the choice of any particular gas are discussed … [cont.].